GENDER DIFFERENCE AND COMORBIDITIES IN CHRONIC HEART FAILURE PATIENTS - R. T. Shukurov; T. A. Abdullaev (Кардиоваскулярная терапия и профилактика)
Aim. Investigation and analysis of clinical-hemodynamic signs of chronic heart failure (CHF) at the age 42-89 y. o., including the assessment of gender and comorbidities, according to ejection fraction (EF) of the left ventricle (LV): preserved EF LV ≥45% (HFpEF) and low EF LV <45% (HFrEF).Material and methods. Totally, 120 CHF patients studied, age 42-89 y. o., with assessment of gender and comorbidities, accoring to ejection fraction (EF) of the left ventricle (LV): preserved EF LV ≥45% (HFpEF) and low EF LV <45% (HFrEF).Results. In most cases the etiology of CHF was coronary heart disease (CHF) — 58,8%, and in 68,3% cases it was comorbid with arterial hypertension (AH). Assessment of CHF in patients with various EF LV showed that in both groups males predominated. In HFrEF there were more overweight patients (41,1%) and in HFpEF — obesity patients (51,6%). In HFrEF patients main factors leading to myocardial impairment were myocardial infarctions in anamnesis (91,1%), and in HFpEF — CHD with AH (81,3%), obesity (51,6%) and diabetes (43,8%). Extracardiac comorbidity in HFrEF was mostly chronic obstructive pulmonary (26,8%) and obliterate atherosclerosis of lower extremities arteries (17,9%), and HFpEF — congestion pneumonia (23,4%) and varicose vein disease (34,4%).Conclusion. Patients with HFrEF — are mostly the CHD patients having risk factors: smoking, alcohol overconsumption, excessive physical exertion. HFpEF patients are mostly CHD+AH, most of them had metabolic disorders. Most cases of varicose vein disease and pneumonia in HFrEF can be explained by obesity and increased rate of diabetes. Cases of vascular dementia in HFpEF patients are related to higher prevalence of AH and its complications.